If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-x+43=2(3x-3)-7
We move all terms to the left:
-x+43-(2(3x-3)-7)=0
We add all the numbers together, and all the variables
-1x-(2(3x-3)-7)+43=0
We calculate terms in parentheses: -(2(3x-3)-7), so:We get rid of parentheses
2(3x-3)-7
We multiply parentheses
6x-6-7
We add all the numbers together, and all the variables
6x-13
Back to the equation:
-(6x-13)
-1x-6x+13+43=0
We add all the numbers together, and all the variables
-7x+56=0
We move all terms containing x to the left, all other terms to the right
-7x=-56
x=-56/-7
x=+8
| 6-3x/2=2 | | -4x+44=5(3x+5) | | 3(4x+3)=4x-47 | | -2x-38=3(2x-2) | | -5x-13=32 | | 12-3(x+6)=-3 | | 1÷4x+3=7 | | 2x-31=5(5x+3) | | -7x-17=-x+13 | | 3x-8=2(x-2)+7 | | 4x+28=4(3x+3) | | 40=4(5x+5) | | 4x+11=-49-4x | | (1-x)/5=(1+2x)/3+x | | 2(3x-3)=x+24 | | 3x+17=3(3x-3)-4 | | x+27=5(3x-3) | | 3x-47=4(3x-5) | | 10=4(3x-5)+6 | | -4x+10=5(5x-3)-4 | | 9h-17=37 | | -34-9x=8+5x | | -38=2(4x+5) | | 3(2x+1)-4=17 | | 2x-65°=x+20° | | -x+41=3(x+3) | | 7x+16=-12 | | 4.2x=-14.7 | | -5-9x=6x+73 | | x+3(-x/3-1)+3=0 | | (3x/x+2)+(6/x)=(12/x^2-2x) | | x-3(-(x/3)-1)+2=0 |